Hubungan Waktu Tunggu Pelayanan Resep Terhadap Kepuasan Pasien di Apotek X di Bukittinggi - Yonrizon, Yonrizon (Neolectura, 2024)
Based on the research results, it shows that the waiting time for prescription services describes the level of efficiency and effectiveness of pharmacy staff in processing prescriptions. Long waiting times can be a component that has the potential to cause patient dissatisfaction. This study aims to determine the relationship between waiting time for drug services and patient satisfaction at Pharmacy X in Bukittinggi. This research is a quantitative study with a cross-sectional, correlative descriptive study design. The sampling technique used accidental sampling technique with a sample size of 75 respondents. Data collection tools use a stopwatch and questionnaires. Analysis uses the chi square test. The research results showed that the majority of respondents' waiting time for prescription services at Pharmacy The results of the analysis show that there is a relationship between waiting time for drug services and patient satisfaction at Pharmacy X in Bukittinggi, with a ? value of 0.000 (<0.05). The results of this study recommend that pharmacies can strive for shorter drug prescription service times so as to increase patient satisfaction.